FAKTOR YANG BERHUBUNGAN DENGAN KESIAPSIAGAAN KEBAKARAN PADA PEKERJA DI BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Erismawati, Ni Kadek Lilis; Adhi, Kadek Tresna (ARCHIVE OF COMMUNITY HEALTH, 2023)
Airport is a workplace that has a potential to cause fires. Even though, protection facility provided, it has still been reported many fires happened recently,because  influenced by preparednes workers. Fire preparedness is disaster management activities to anticipating fires through organizing to help the risky community. This research aims to determine the factors related to the fire preparedness of workers at I Gusti Ngurah Rai International Airport I in Bali. The research design used was quantitative research analytic with cross-sectional study. The samples  were 147 workers of PT. Angkasa Pura 1 involved who were selected using  accidental sampling technique. It was conducted during May to June on 2020. Data research instrument used was questionnaire which was analyzed in univariate, bivariate and multivariate ways. The results revealed that 51.70% of respondents had good preparedness. There was a significant relationship among  all variables of individual factors and management factors on fire preparedness (p<0.05). Multivariate analysis showed that the variable of unsafe condition prevention effort was a variable that had the strongest influence. As an effort to improve preparedness, it is expected to provide socialization of SOP and workers training of facing fires. Keywords : Preparedness, Fire, Airport, Worker